THE MEANING OF SLANG LANGUAGE IN 22 JUMP STREET MOVIE - Eren Julianto Gultom; Anni Holila Pulungan (State University of Medan, 2015)
This research focused on the meaning of slang language used by the characters in 22Jump Street Movie. The research was conducted by using qualitative method. Thedata were collected from the movie script. The objective of the study was to find outthe meaning of the slang language used by the characters in 22 Jump Street Movieand also the reason why the characters used the slang language. The data were takenfrom the movie script which was downloaded from the internet. The data wereanalyzed by using Eric Partridge’s theory about slang. The result showed that themeaning used by the characters were contextual meaning, depending on the situationor given context of the scene. The result show that only several slang language thathave literal meaning. The reason of using slang language in this research was toreduce seriousness of the conversation since the movie was a comedy-action genre inwhich the comedy and action must be appeared at the same time.